Cardiac CT in Infective Aortic Prosthetic Valve Endocarditis - Marwan Nadiri; Ana Falticeanu; Olivier Lebecque (Journal of the Belgian Society of Radiology)
Teaching point: Cardiac computed tomography angiography is particularly valuable in patients with prosthetic valve infective endocarditis who have contraindications to transesophageal echocardiography (TOE), or when TOE is limited by heavy calcifications or the prosthetic valve, offering at least equivalent sensitivity for detecting abscesses and pseudoaneurysms.